Accounting for What Matters to Patients in the G-DRG System: A Stakeholder's Perspective on Integrating Functioning Information. (August 2018) - Hopfe, Maren; Stucki, Gerold; Bickenbach, Jerome E; Prodinger, Birgit
Functioning information constitutes a relevant component for determining patients' service needs and respective resource use. Diagnosis-Related Group (DRG) systems can be optimized by integrating functioning information. First steps toward accounting for functioning information in the German DRG (G-DRG) system have been made; yet, there is no systematic integration of functioning information. The G-DRG system is part of the health system; it is embedded in and as such dependent on various stakeholders and vested interests. This study explores the stakeholder's perspective on integrating functioning information in the G-DRG system. A qualitative interview study was conducted with national stakeholders in 4 groups of the G-DRG system (health policy, administration, development, and consultations). Interviews were analyzed using inductive thematic analysis. In total, 14 interviews were conducted (4 administration and 10 consultation group). Three main themes were identified: (1) functioning information in the G-DRG system: opportunities and obstacles, (2) general aspects concerning optimizing G-DRG systems by integrating additional information, and (3) ideas and requirements on how to proceed. The study offers insights into the opportunities and obstacles of integrating functioning information in the G-DRG system. The relevance of functioning information was evident. However, the value of functioning information for the G-DRG system was seen critically. Integrating functioning information alone does not seem to be sufficient and a systems approach is needed.